2000
DOI: 10.1074/jbc.m000091200
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Tissue Transglutaminase in Ethanol-induced Inhibition of Hepatocyte Proliferation and α1-Adrenergic Signal Transduction

Abstract: The mechanisms by which ethanol inhibits hepatocyte proliferation have been a source of some considerable investigation. Our studies have suggested a possible role for tissue transglutaminase (tTG) in this process. Others have shown that tTG has two distinctly different functions: it catalyzes protein cross-linking, which can lead to apoptosis and enhancement of extracellular matrix stability, and it can function as a G protein (G␣ h ). Under that circumstance, we speculated that the cross-linking activity wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 36 publications
(37 reference statements)
3
33
0
2
Order By: Relevance
“…Collagen crosslinking makes this molecule more resistant to collagenase degradation, therefore inhibiting fibrosis remodeling. In agreement with other reports (5,20), our results showed that the persistent presence of tTG after withdrawal of toxic agents might determine a point of "no return" for hepatic cirrhosis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Collagen crosslinking makes this molecule more resistant to collagenase degradation, therefore inhibiting fibrosis remodeling. In agreement with other reports (5,20), our results showed that the persistent presence of tTG after withdrawal of toxic agents might determine a point of "no return" for hepatic cirrhosis.…”
Section: Discussionsupporting
confidence: 82%
“…This reaction leads to production of oxidative radicals that cause lipid peroxidation and, consequently, hepatotoxic injury (7). Ethanol also induces synthesis of type I collagen fibrils (18,19), inhibition of hepatocyte proliferation (20)(21)(22), exacerbation of activity in hepatic stellate cells (20,23), and increased expression of tissue transglutaminase (tTG) (24). Since a mechanism that renders matrix resistant to degradation results from the formation of ε-(γ-glutamyl) lysine cross-links by tissue transglutaminase (5,25,26), use of the hepatotoxic agents in combination could be more effective in maintaining the fibrotic pattern.…”
Section: Introductionmentioning
confidence: 99%
“…One may then postulate that this signaling pathway participates to the myometrial cell hypertrophy or proliferation that occurs during this period. Indeed, Gha protein was shown to mediate a1-AR-induced hepatocyte proliferation (Wu et al 2000) and activation of extracellular signal-regulated kinases in neonatal rat cardiomyocytes (Lee et al 2003). In agreement with these results, we have recently shown that Gha protein participates to the a1-AR-mediated regulation of smooth muscle cell proliferation (Dupuis et al 2004).…”
Section: Discussionsupporting
confidence: 76%
“…tTG Assay-The tTG activity was measured by analyzing the incorporation of [1,[4][5][6][7][8][9][10][11][12][13][14] C]putrescine dihydrochloride into proteins (31)(32)(33). Cells were treated with CalC or serum-deprived and then lysed in Tris-buffered saline containing 0.5% Nonidet P-40 and 1 mM phenylmethylsulfonyl fluoride.…”
Section: Methodsmentioning
confidence: 99%